The Effectiveness of the STEAM Approach in Elementary Education: A Systematic Literature Review - nukhbatul bidayati haka; Edo Wijaya; Ayu Shafa Salsabila (Universitas Negeri Surabaya, 2025)
This study aims to analyse the effectiveness of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach in elementary education through a systematic literature review based on the PRISMA 2020 framework. Using Publish or Perish software, 996 studies were initially identified from Google Scholar, and 27 empirical articles published between 2021 and 2024 met the inclusion criteria. The analysis revealed that STEAM-based learning significantly improved students’ critical thinking (N-Gain = 0.48–0.86), problem-solving (t = 2.874 > 1.980), creativity, and learning motivation (increase of 76-93%). The integration of STEAM with models such as Project-Based Learning (PjBL), Guided Inquiry, and Augmented Reality media enhanced contextual understanding and engagement. Findings demonstrate that STEAM is a flexible and transformative educational framework that bridges cognitive, affective, and psychomotor domains. These results contribute to curriculum innovation, offering practical implications for teachers, policymakers, and curriculum designers in promoting 21st-century learning competencies.